HISTOLOGICAL ANALYSIS OF IN VITRO CULTURED COCONUT ENDOSPERM - Lazarus Agus Sukamto (SEAMEO BIOTROP, 2017)
Coconut is an important plant for supporting the livelihood of people in tropical regions and is often regarded as a symbolic icon of the tropics. However, coconut fruits are large and heavy, posing a risk of injury when falling and hitting individuals standing beneath the tree. To prevent such accidents, ripe fruits must be harvested regularly. Coconut trees derived from in vitro–cultured endosperm are triploid and produce seedless fruits (without endocarp), which are significantly lighter and therefore safer. The objective of this study was to investigate plant regeneration from fresh and in vitro–cultured coconut endosperms. Both types of endosperm tissues were analyzed using histological methods. Solid endosperm from a seven-month-old post-anthesis coconut of the ‘Samoan Dwarf’ cultivar was collected and cultured in vitro using a modified Branton and Blake medium. Histological observations of fresh coconut endosperm revealed relatively uniform parenchyma cells in both size and shape, with nuclei containing one to five nucleoli. In contrast, three-month-old calli obtained from in vitro–grown endosperm in semi-solid medium displayed cells with diverse shapes and sizes, a high nucleus-to-cytoplasm ratio, and abundant starch, protein, and lipid deposits, indicating active cell division. Furthermore, seven-month-old calli grown in liquid medium contained embryogenic cells resembling proembryos. Fourteen-month-old bud-like structures developed in semi-solid medium showed clear histological features, including a meristematic layer, tunica–corpus organization, cortex-like region, and xylem tracheids. These findings indicate that the bud-like structure represents an early stage of shoot-bud formation in coconut endosperm. To our knowledge, this is the first report demonstrating early shoot-bud formation in coconut endosperm cultured in vitro.